PROJECT “BULGARIAN LITERATURE FOR CHILDREN AND YOUTH XX–XXI C.” - Alexandra Antonova (Издател, 2025)
The text presents the idea and the main directions of work of “Bulgarian Literature for Children and Adolescents of the 20th–21st Centuries” project, demonstrates its interdisciplinary nature, which combines literary, archival and psychodramatic approaches to our literature for children. The presentation reproduces the project model of a multi-faceted approach to literary heritage, which considers texts aesthetically, psychologically, pedagogically, methodologically, illustratively and generationally, seeking the dynamics and definition of both the canon itself and the concept of canon. Accent of the present text is the concept and the organization of the upcoming “Contemporary Bulgarian Literature for Children and Adolescents” Round Table.